A novel approach to estimate the local population denominator to calculate disease incidence for hospital-based health events in England. (11th July 2022) - Campling, James; Begier, Elizabeth; Vyse, Andrew; Hyams, Catherine; Heaton, Dave; Southern, Jo; Finn, Adam; Madhava, Harish; Gessner, Bradford D.; Ellsbury, Gillian
Abstract: While incidence studies based on hospitalisation counts are commonly used for public health decision-making, no standard methodology to define hospitals' catchment population exists. We conducted a review of all published community-acquired pneumonia studies in England indexed in PubMed and assessed methods for determining denominators when calculating incidence in hospital-based surveillance studies. Denominators primarily were derived from census-based population estimates of local geographic boundaries and none attempted to determine denominators based on actual hospital access patterns in the community. We describe a new approach to accurately define population denominators based on historical patient healthcare utilisation data. This offers benefits over the more established methodologies which are dependent on assumptions regarding healthcare-seeking behaviour. Our new approach may be applicable to a wide range of health conditions and provides a framework to more accurately determine hospital catchment. This should increase the accuracy of disease incidence estimates based on hospitalised events, improving information available for public health decision making and service delivery planning.